Genetic and epigenetic regulation of growth, reproduction, disease resistance and stress responses in aquaculture - Liu, Zhanjiang; Zhou, Tao; Gao, Dongya (Frontiers in Genetics, 2022)
Major progress has been made with genomic and genetic studies in aquaculture in the last decade. However, research on epigenetic regulation of aquaculture traits is still at an early stage. It is apparent that most, if not all, aquaculture traits are regulated at both genetic and epigenetic levels. This paper reviews recent progress in understanding of genetic and epigenetic regulation of important aquaculture traits such as growth, reproduction, disease resistance, and stress responses. Although it is challenging to make generalized statements, DNA methylation is mostly correlated with down-regulation of gene expression, especially when at promoters and enhancers. As such, methylation of growth factors and their receptors is negatively correlated with growth; hypomethylation of genes important for stress tolerance is correlated with increased stress tolerance; hypomethylation of genes important for male or female sex differentiation leads to sex differentiation into males or females, respectively. It is apparent that environmental regulation of aquaculture traits is mediated at the level of epigenetic regulation, and such environment-induced epigenetic changes appeared to be intergenerationally inherited, but evidences for transgenerational inheritance are still limited.